Separation of Multi-Material Polymer Combinations Produced by Joining Using Pin-like Structures - Wolf, Michael; Drummer, Dietmar (Journal of Manufacturing and Materials Processing, 2022)
In industrial applications, multi-material joints are becoming increasingly important to achieve a sustainable and resource-saving production. Not only high mechanical properties during the component use have to be given, but also possibilities to separate the joint after end of life are crucial. The recycling and re-use of the materials plays an increasing role in the process chain. Conventional multi-material joints can be separated by cutting out the joining zone, solvents, or thermal degradation. However, these methods result in a loss of material, damage to the base material, or high energy consumption. Therefore, novel joining methods are desirable, such as the joining using pin-like structures. The potential of this novel method for joining adhesion incompatible materials has been demonstrated in previous studies. This paper studies the separability of these connections. Therefore, joints between polyamide 66 (PA66) and polypropylene (PP) as well as PA66 and polymethylmethacrylate (PMMA) are investigated by means of thermal separation and shredding with subsequent sorting using the density difference of the materials. The separated components were investigated by analytical methods (including dissolution tests, viscosity number analysis, and Fourier-transform infrared spectroscopy) with respect to varietal purity and possible degradation effects. It could be shown that shredding allows a complete separation of the multi-material joint into its individual components without material residues or material loss. For thermal separation, material residues of PP or PMMA could be detected in the pin gaps of the PA66. For both separation methods, an influence on the base materials due to degradation effects could be excluded. It can be stated that joining using pin-like structures in vibration welding technology offers a sustainable production of multi-material joints with high recyclability.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Disassembling; Joining; Multi-material; Pin-like structures; Recycling; Separation